2021
DOI: 10.3390/nano11102631
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Fiber Reinforced Composites: Study of Modification Effect on Weathering-Induced Ageing via Nanoindentation and Deep Learning

Abstract: The exposure of carbon-fiber-reinforced polymers (CFRPs) to open-field conditions was investigated. Establishment of structure–property relations with nanoindentation enabled the observation of modification effects on carbon-fiber interfaces, and impact resistance. Mapping of nanomechanical properties was performed using expectation-maximization optimization of Gaussian fitting for each CFRPs microstructure (matrix, interface, carbon fiber), while Weibull analysis connected the weathering effect to the statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…CNTs can be further assembled into macroscopic materials, such as carbon nanofibers (CNFs), which find many uses, especially in high-performance composites and energy devices [ 332 , 333 , 334 , 335 , 336 ]. In this case, they have been decorated with Fe(III) complexes to mimic oxidases [ 337 ], peroxidases, and catalases for sensing and environmental technology [ 338 ].…”
Section: Cnms For Enzyme Mimicry Inhibition or Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…CNTs can be further assembled into macroscopic materials, such as carbon nanofibers (CNFs), which find many uses, especially in high-performance composites and energy devices [ 332 , 333 , 334 , 335 , 336 ]. In this case, they have been decorated with Fe(III) complexes to mimic oxidases [ 337 ], peroxidases, and catalases for sensing and environmental technology [ 338 ].…”
Section: Cnms For Enzyme Mimicry Inhibition or Monitoringmentioning
confidence: 99%
“…Fullerene derivatives have been envisaged for the inhibition of a variety of enzymes, including recent examples of HIV-1 protease [346], ribonuclease A [347], glycosidases CNTs can be further assembled into macroscopic materials, such as carbon nanofibers (CNFs), which find many uses, especially in high-performance composites and energy devices [332][333][334][335][336]. In this case, they have been decorated with Fe(III) complexes to mimic oxidases [337], peroxidases, and catalases for sensing and environmental technology [338].…”
Section: Cnms As Enzyme Inhibitorsmentioning
confidence: 99%
“…Koumoulos et al showed that carbon fibers added into poly­(methacrylic acid) (PMAA) reinforced the interphasial properties. The modified PMAA had the unique molecular weight of grafted macromolecules and different chain-length brushlike structures, which enabled the composite to maintain better mechanical properties after weathering . Zhang et al introduced hyperbranched polysiloxane (HBPSi) to poly­(amic acid) (PAA) through chemical bonds between the amino groups of HBPSi and reactive sites of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond process control, AI and machine learning hold a lot of promise to bridge this gap with their empirical character, as till today rapid characterization tools have been exploited with high accuracy for the discovery of materials and immunotherapies, materials reinforcement/failure/toxicity mechanism recognition, structural characterization, phase detection and quantification, and anomaly detection [ 3 , 25 , 31 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. While machine learning and AI are already well established in the fields of statistics, economics, and bioinformatics, their utilization in nanotechnology is relatively new [ 44 ].…”
Section: Introductionmentioning
confidence: 99%